COMMUNICATION IN THE SOCIALIZATION PROCESS OF STUDENTS - Gavhar Normurodova (Scholar Express Journal, 2023)
Communication is of great importance in the comprehensive formation of a person. To learn simple things, it is necessary to communicate through imitation. Relationships develop based on the rules of society. A huge difference can be seen between individual and person communication. For example, there is a big difference between the communication of a child, a mentally ill person, and a person with a low level of consciousness, and a mature person with a high level of consciousness.
Keywords: Pedagogy; method; methodology